Characteristics and outcomes of AED use in pediatric cardiac arrest in public settings: The influence of neighborhood characteristics. (1st January 2020) - Griffis, H.; Wu, L.; Naim, M.Y.; Bradley, R.; Tobin, J.; McNally, B.; Vellano, K.; Quan, L.; Markenson, D.; Rossano, J.W.
Abstract: Background: Automated external defibrillators (AEDs) are critical in the chain of survival following out-of-hospital cardiac arrest (OHCA), yet few studies have reported on AED use and outcomes among pediatric OHCA. This study describes the association between bystander AED use, neighborhood characteristics and survival outcomes following public pediatric OHCA. Methods: Non-traumatic OHCAs among children less than18 years of age in a public setting between from January 1, 2013 through December 31, 2017 were identified in the CARES database. A neighborhood characteristic index was created from the addition of dichotomous values of 4 American Community Survey neighborhood characteristics at the Census tract level: median household income, percent high school graduates, percent unemployment, and percent African American. Multivariable logistic regression models assessed the association of OHCA characteristics, the neighborhood characteristic index and outcomes. Results: Of 971 pediatric OHCA, AEDs were used by bystanders in 10.3% of OHCAs. AEDs were used on 2.3% of children ≤1 year (infants), 8.3% of 2–5 year-olds, 12.4% of 6−11 year-olds, and 18.2% of 12–18 year-olds (p < 0.001). AED use was more common in neighborhoods with a median household income of >$50, 000 per year (12.3%; p = 0.016), <10% unemployment (12.1%; p = 0.002), and >80% high school education (11.8%; p = 0.002). Greater survival to hospital discharge and neurologically favorable survival were among arrests with bystander AED use, varying by neighborhood characteristics. Conclusions: Bystander AED use is uncommon in pediatric OHCA, particularly in high-risk neighborhoods, but improves survival. Further study is needed to understand disparities in AED use and outcomes.